2011
DOI: 10.9738/cc53.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lichtenstein and Laparoscopic Transabdominal Preperitoneal Repair of Recurrent Inguinal Hernias

Abstract: The aim of our study was the comparative analysis of the results of two surgical methods: tension-free repair by the Lichtenstein technique and laparoscopic transabdominal preperitoneal (TAPP) repair. In total 52 patients with recurrent inguinal hernia were randomly assigned to the two groups: Lichtenstein (28 patients) and TAPP (24 patients). Comparisons between these groups were done by several preoperative, intraoperative, and postoperative factors. For postoperative factors both short-term and long-term re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…However, one of these studies used in the open group a preperitoneal mesh according to the Stoppa technique [16]. Therefore, we performed for the endpoints recurrence and chronic pain (C3 years) a new meta-analysis (random model) only including the 3 studies comparing Lichtenstein vs. endoscopic repair and including another RCT published recently [17]. This analysis shows that there is also an advantage for the endoscopic approach with respect to chronic pain (Fig.…”
Section: Recurrent Hernias After Conventional Open Repairmentioning
confidence: 99%
“…However, one of these studies used in the open group a preperitoneal mesh according to the Stoppa technique [16]. Therefore, we performed for the endpoints recurrence and chronic pain (C3 years) a new meta-analysis (random model) only including the 3 studies comparing Lichtenstein vs. endoscopic repair and including another RCT published recently [17]. This analysis shows that there is also an advantage for the endoscopic approach with respect to chronic pain (Fig.…”
Section: Recurrent Hernias After Conventional Open Repairmentioning
confidence: 99%
“…All the RCTs included in that meta-analysis compared the laparo-endoscopic procedures with the open Lichtenstein technique. Three RCTs compared the Lichtenstein operation with TAPP (13,15,17), two RCTs compared it with TEP (11,16), and two RCTs compared it with both TEP and TAPP (12,14).…”
mentioning
confidence: 99%
“…The meta-analysis by Pisanu (8) contained the largest number of exclusively prospective randomized trials (RCTs) (11,12,13,14,15,16,17). All the RCTs included in that meta-analysis compared the laparo-endoscopic procedures with the open Lichtenstein technique.…”
mentioning
confidence: 99%
“…A definition of CPIP was lacking in 31 (39%) of the studies (table 2) [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]. In the other 49 studies (61%), a total of 22 different definitions of CPIP were identified.…”
Section: Resultsmentioning
confidence: 99%
“…In half of the studies, the categorization consisted of reporting the effect of CPIP on daily life using 9 different validated or nonvalidated criteria (table 3) [33,40,48,52,58,61,62,68,73,79,86]. The remaining studies used a categorization of pain severity based on VAS or numerical analog scale measurements [8,10,19,22,23,50,56,71,73,81,87,88,89]. The subsequent categorization of PI was highly heterogeneous (fig.…”
Section: Resultsmentioning
confidence: 99%